Medical Record Document Storage Room Design to Support Service Quality at The Inpatient Clinic of Aisyiyah Pandaan: Desain Ruang Penyimpanan Dokumen Rekam Medis untuk Menunjang Kualitas Pelayanan di Klinik Rawat Inap Aisyiyah Pandaan - Nisak , Umi Khoirun; Widoawati, Hesty; Cholifah (Universitas Muhammadiyah Sidoarjo, 2022)
Primary care data collected from medical records is very interesting because this data is a synthesis of the patient's history and also provides a comprehensive picture of the patient's health status. This data can also be used as evidence and law enforcement related to the care received by patients, as a basis for treatment costs and health statistical data. This data is managed in a good Medical Records management. Aisyiyah Pandaan Inpatient Clinic is a clinic that does not yet have adequate medical record management. The availability of this data is less than optimal because the data source or medical record storage area does not exist. The activities of filling, assembling, evaluating the quality of medical record data, as well as retention were also not carried out due to the lack of knowledge regarding inpatient medical record management at the clinic level. These weaknesses can be overcome by the presence of a room that is not functionally optimal and the presence of resources in carrying out medical record management activities. The need for shelves that will be used for the next 2 years is 3 iron shelves measuring 2 m long, 40 cm wide with 5 shaff and 2 face rack types. The space requirement for storage of medical record files with iron racks is 9 m2.